Features of judicial examination of computer technologies (Journal of actual problems of jurisprudence, 2018)
This article discusses the features of forensic computing. The opinions of various authors on this type of examination. The methods and objects and differences forensic computer technology from other related types of forensics.Key words: forensics, especially scientific knowledge, computer technology, storage media, information system.